Constituents and relations in sentences and discourse - Garrido, Joaquín; Rodríguez Ramalle, Teresa María (Círculo de Lingüística Aplicada a la Comunicación, 2015)
According to the discourse constituent structure hypothesis (Garrido 2013), there is continuity between sentence and discourse in formal terms, since sentences are elementary discourse units linked by means of coordinating and subordinating discourse relations. This continuity holds between independent sentences and subordinate clauses (Rodríguez Ramalle 2013), so that conjunctions in independent structures have the same properties they have in subordinate ones, and they refer either to a preceding discourse, to a previous communicative situation, or to previously acquired knowledge. Going beyond the sentence, discourse relations are shown to link sentences taken as discourse units, so that a discourse constituent structure is developed where in a configurational approach problems like crossing or multiple relations are solved. Discourse topic management and frames as well as scope relations in discourse constituent structures are thus used to solve the paradox of multiple interpretations for a given discourse.
Keywords: conjunctions; discourse constituent structure; discourse topic management; frames; scope; subordination.